PERAN KEADILAN DAN PEMBAGIAN INFORMASI DALAM HUBUNGAN ANTARA PARTISIPASI ANGGARAN DAN KINERJA KARYAWAN - Wangsa, Evelyn Stefanie; SeTin, SeTin (Jurnal Riset Akuntansi, 2025)
This study aims to analyze the effect of budget participation, procedural justice, and information sharing on employee performance. By examining these three factors, the research seeks to understand how budget involvement influences employees' effectiveness in achieving organizational goals.  The research was conducted using primary data collected through an online questionnaire distributed to 158 managers from trading, manufacturing, and service companies in West Java who were actively involved in budgeting. The data was analyzed using Partial Least Square (PLS) techniques with a structural equation model (SEM) approach to ensure the validity and reliability of the findings.  The results indicate that budget participation, procedural justice, and information sharing positively impact employee performance. Moreover, the relationship between budget participation and employee performance is mediated by the role of information sharing and procedural justice, highlighting the importance of a fair and transparent budgeting process.  However, this study has certain limitations. It employs a cross-sectional design, meaning that data was collected at a single point in time, reflecting only a specific period's circumstances. Despite this limitation, the study provides valuable insights for management in enhancing employee performance through effective budgeting practices. Additionally, these findings can assist accountants and managers in designing budget systems that are more adaptive to employee needs and better aligned with organizational objectives.Keywords: Budget Participation, Procedural Fairness, Information Sharing, Employee Performance